1930
DOI: 10.1113/jphysiol.1930.sp002623
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative observations on thyroxine and allied substances

Abstract: IT was thought desirable to amplify by other methods the results obtained with tadpoles(1) in the study of the effects of natural and synthetic thyroxine and of various intermediate and related compounds prepared by Dr C. R. Harington. For this purpose it was decided to measure their action in increasing the gaseous metabolism of mammals.In the early investigations of the effects of thyroid preparations, an account of which will be found in Grafe's monograph(2), no attempt was made to obtain quantitative resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1933
1933
1963
1963

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…It is therefore possible to distinguish between periods of activity and rest and hence make an estimate of basal metabolic rate (B.M.R.). This was done wherever possible according to the following convention, which was used by Gaddum (1930). A total time of 20 min was assembled, usually of four periods of 5 min, picked out with dividers from those periods showing no disturbance of the record due to movement, and giving the lowest rates of oxygen consumption.…”
mentioning
confidence: 99%
“…It is therefore possible to distinguish between periods of activity and rest and hence make an estimate of basal metabolic rate (B.M.R.). This was done wherever possible according to the following convention, which was used by Gaddum (1930). A total time of 20 min was assembled, usually of four periods of 5 min, picked out with dividers from those periods showing no disturbance of the record due to movement, and giving the lowest rates of oxygen consumption.…”
mentioning
confidence: 99%
“…Six Perspex cylinders are set horizontally between two long sides, with the ends just short of the outer faces. These cylinders form the outer walls of the six metabolism chambers (1)(2)(3)(4)(5)(6) and are covered by circular Perspex plates 5 in. in diameter.…”
Section: Construction Of the Apparatus (Figs 1 And 2)mentioning
confidence: 99%
“…Since, on the basis of equivalent iodine contents, the effect of this polypeptide was the same as that of Squibb's thyroxine (Salter, Lerman and Means (1932)), which is racemic (Kendall (1931)), it would seem that optical activity may be disregarded in the interpretation of our data. There remain the observations of Gaddum (1930) on four rats, which led him to the conclusion that 1-thyroxine is two and one-half times as effective as d-thyroxine. While we feel that his observations are inadequate to support such an important conclusion, our data, for purposes of completeness, may be considered in the light of his findings.…”
Section: Introductionmentioning
confidence: 99%
“…Gaddum (1930), using material supplied to him by Harington, concluded that levorotatory thyroxine had about two and one-half times as much effect on the oxygen consumption of a normal rat as the dextro-form. Harington and Salter (1930) showed that the levorotatory form, isolated by means of tryptic digestion, was the naturally occurring variety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation